STRATEGI PENGEMBANGAN WISATA PARALAYANG DI KOTA BATU - Achmad Yanu Alif Fianto; Martinus Sony Erstiawan; Rudi Santoso (Majalah Ekonomi, 2021)
While promotion strategies such as emphasizing natural attractions, the arts, and culture may be used to sell their tourist goods, their commodities in the shape of natural attractions, the arts, and culture are good, and the entire spectrum of tourist options is available.. The purpose of this study is to identify the characteristics of tourist-friendly natural sites and to investigate potential marketing applications for this target group using various promotional strategies. This study used a qualitative methodology with a case study approach, focusing on natural attraction marketing strategies. Domain analysis was used to analyse the data. The approach verifies the data's validity by using a variety of data verification methods, one of which is triangulation and data verification on the interview and documentation. To create a successful marketing plan, they needed to gather all they could about the topic. Tourism Marketing Model: A promotion strategy to draw people in. Arts and culture visits as well as nature tourism may all be part of an extended vacation. An aggressive technique called the Promotion Mix helps boost domestic and international visits.